Basin‐Scale River Runoff Estimation From GRACE Gravity Satellites, Climate Models, and In Situ Observations: A Case Study in the Amazon Basin. Issue 10 (7th October 2020) - Chen, Jianli; Tapley, Byron; Rodell, Matt; Seo, Ki‐Weon; Wilson, Clark; Scanlon, Bridget R.; Pokhrel, Yadu
Abstract: River runoff is estimated as a water budget residual using Gravity Recovery and Climate Experiment (GRACE) terrestrial water storage time series, ERA5 reanalysis data, and precipitation observations for January 2003 through December 2015 for the Obidos upstream drainage basin and for the entire Amazon basin. Estimated runoff based on the water budget agrees remarkably well with in situ gauge observations at Obidos, especially at seasonal time scales, with nearly perfect phase agreement but slightly larger seasonal amplitude. The discrepancy in the seasonal amplitude may be attributed to underestimation of river gauge runoff during the wet season when water overflows the riverbanks. The ERA5 model appears to overestimate long‐term mean evapotranspiration in the Amazon by ~2 cm/month based on comparisons with precipitation and runoff observations. Using precipitation data based on satellites and gauge observations relative to gauge observations alone improved agreement between water budget runoff estimates and in situ runoff observations. Seasonal variations in ERA5‐simulated runoff are about twice as large as those from in situ observations and show a large phase lag as well. Water budget‐based runoff for the entire Amazon (~7, 200 km 3 averaged over the 13‐year period) is significantly larger than observed runoff (~5, 700 km 3 ) at Obidos and notably larger than previous estimates for the entire Amazon. These differences may be partly related to submarine runoff from the Amazon basin that cannot be captured by surface gauges. Key Points: We provide a new estimate of seasonal and yearly river runoff changes for the Amazon basin using the water budget closure method The water budget closure estimates remarkably agree well with in situ observations in the Amazon basin at seasonal scales We have demonstrated that water budget closure method has the potentials to detect submarine runoff from the Amazon basin